The Internalisation of Islamic Values Through the Habituation Method Among Pupils - Muhamad Ulul Azmi; Muhammad Burhanudin; Muhammad Habibulloh; Erpan Padilah; Arif Rahman Hakim (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2025)
The internalisation of Islamic values is a strategic endeavour in shaping the religious character of pupils at madrasahs. This study aims to analyse the implementation of the habituation method in the internalisation of Islamic values and to identify the factors that support and hinder its implementation at MTs Raden Rahmat Selorejo Mojowarno. The study employs a qualitative approach using a case study design. Data were collected through interviews, observations and documentation involving the headteacher, the deputy head for student affairs, teachers and pupils. Data analysis was carried out using the Miles and Huberman interactive model. The research findings indicate that the internalisation of Islamic values is carried out through the regular practice of congregational prayer, recitation of the Qur’an, istighasah, tahlil, and respect for teachers. These activities integrate the internalisation of values of worship, socio-religious values, and moral conduct, ensuring that Islamic values are not merely understood cognitively but are also manifested in pupils’ daily behaviour. The programme’s success is underpinned by the madrasah’s commitment, its religious culture, the exemplary conduct of teachers, and a system of continuous supervision and guidance. Meanwhile, the main obstacle stems from the low level of discipline among some pupils in consistently participating in the habit-forming activities. This study indicates that the habit-forming method is effective in strengthening pupils’ religious character and can serve as a reference for madrasahs in developing character education based on Islamic values